1976
DOI: 10.1002/1097-0142(197602)37:2<853::aid-cncr2820370234>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Chronic neurologic disturbance in childhood leukemia

Abstract: Twenty-three leukemic children were studied prospectively to detect chronic effects of therapy. All patients received CNS prophylaxis, including 2400 R cranial irradiation, and intermittent maintenance therapy with intravenous methotrexate, cyclophosphamide and cytosine arabinoside. Neurologic symptoms were observed in 12 patients, all of whom had intermittent limping and mild incoordination, between the 10th and 18th month of maintenance therapy. Five of the 12 sustained seizures and four of these had subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Since the early 1980s, alternative protocols have been developed involving a combination of chemo‐agents including neurotoxic methotrexate 4. Early computed tomography (CT) and magnetic resonance imaging (MRI) studies with populations of children who received both chemotherapy and irradiation reported ventricular dilation, cortical calcification, and atrophy 5–7 that were more severe compared to children who received chemotherapy only 1. Neuroimaging findings varied, however, from no significant brain abnormalities 8, to transient white matter changes in a small percentage of ALL survivors 9, and to significant widening of the sulci and ventricle in children receiving exclusively chemotherapy 10.…”
Section: Introductionmentioning
confidence: 99%
“…Since the early 1980s, alternative protocols have been developed involving a combination of chemo‐agents including neurotoxic methotrexate 4. Early computed tomography (CT) and magnetic resonance imaging (MRI) studies with populations of children who received both chemotherapy and irradiation reported ventricular dilation, cortical calcification, and atrophy 5–7 that were more severe compared to children who received chemotherapy only 1. Neuroimaging findings varied, however, from no significant brain abnormalities 8, to transient white matter changes in a small percentage of ALL survivors 9, and to significant widening of the sulci and ventricle in children receiving exclusively chemotherapy 10.…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric patients subjected to a combination of these therapeutic modalities may be at risk of neurological and neuropsychological impairment. Studies of long-term survivors of childhood acute lymphoblastic leukemia (ALL) have shown that central nervous system (CNS) preventive therapy is associated with transient as well as permanent neurological disturbances, including neuropsychological deficits of varying degrees (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…The neurological impairments include transient incoordination and paraplegia, seizures, learning disorders and fatal leucoencephalopathy (Meadows & Evans, 1976;Bleyer et al, 1973;McIntosh et al, 1976). Other less frequent toxic effects of methotrexate include bone pain, osteoporosis and pulmonary fibrosis.…”
mentioning
confidence: 99%